The effectiveness of the formation of logistics relations in modern geopolitical conditions, problems and their legal regulation - Tokatov, R.A.; Sabyrzhan, A. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the research in the article is to study the economic and legal aspects of the transport and transit potential of Kazakhstan, to determine to the state its economic efficiency and the possibilities of legal regulation mechanisms. The research uses fundamental and applied, legal comparisons, legal statistical, system, logical, functional methods of scientific research. The main directions of determining the transport and transit potential of Kazakhstan and the development of law enforcement practice. Foreign experience has been studied, the legal foundations of the legislation of Kazakhstan for the introduction of effective economic and legal mechanisms have been studied. The mechanisms and directions of the formation of legitimate conditions that provide a comfortable opportunity for their development will be studied by studying the circumstances that served as the basis for making a profit to the domestic economy through the development of the transport and transit potential of Kazakhstan. The conclusions drawn as a result of the study are that in order to obtain maximum profit from the state through the development of transport and transit potential of Kazakhstan, it is necessary to create a legal framework regulating the correct and effective use of international transport corridors passing through the territory of the country. Inefficient legal mechanisms in the development of Kazakhstan's transport and transit potential do not allow the application of legal norms. Therefore, it is very important at the present stage to finally consider the basics of legal regulation of logistics relations serving international cargo transportation in Kazakhstan, and pay special attention to conducting scientific research in this direction. The practical significance of the study lies in the fact that in order to develop the transport and transit potential of Kazakhstan, it is necessary to implement the state measures taken and, as a result, create the foundations of socio-economic development. The results of the study will allow improving relations in the provision of logistics services for international cargo transportation for the full use of the transport and transit potential of Kazakhstan.